Determinants of Muntok White Pepper Export Value to Singapore and the United States - Lingga Saptarini; Dwi Rachmina; Suprehatin Suprehatin (Universitas Panji Sakti, 2026)
This study analyzes the factors influencing the export value of Muntok White Pepper (MWP) from the Bangka Belitung Islands Province to its main export destinations, Singapore and the United States, from 2010 to 2023. Panel data regression with a fixed effects model is used to combine production, exchange rate, and domestic price variables with export prices and trade policies. The analysis results indicate that production, exchange rate, export price, and non-tariff barriers (NTB) policies play a significant role in affecting export value, while domestic prices do not exert a significant influence. Elasticity analysis results in the exchange rate being the most responsive factor in influencing export value. Methodologically, this study presents the interpretation of panel data regression coefficients based on elasticity to measure export responsiveness, an approach not commonly applied in agricultural trade analysis. Contextually, this study emphasizes the strategic role of Muntok White Pepper as a geographically indicated commodity in supporting the competitiveness of Indonesian spice exports. These findings provide empirical evidence and policy insights for strengthening export resilience through increased production, exchange rate management, and compliance with international trade standards.